Comparison of windup and stretch pitching biomechanics in baseball with implications for safety and performance - Fleisig, G. S.; Slowik, J. S.; Kutz, C. B.; Escamilla, R. F. (The American Journal of Sports Medicine, 2024)
Background Historically, it was assumed by some that high leg lift with windup pitching generated more ball velocity whereas pitching from the stretch was quicker to reduce the risk of base stealing but also more stressful on the arm. However, many now believe that velocity and stress do not differ between windup and stretch and always pitching from the stretch is simpler than mastering 2 techniques.